Aloe vera assisted facile green synthesis of reduced graphene oxide for electrochemical and dye removal applications. Issue 43 (18th May 2017) - Bhattacharya, Gourav; Sas, Shrawni; Wadhwa, Shikha; Mathur, Ashish; McLaughlin, James; Roy, Susanta Sinha
Abstract : In the present work, the suitability of Aloe vera (AV) as a 'green reducing agent' has been investigated for the reduction of graphene oxide (GO). Abstract : In the present work, the suitability of Aloe vera (AV) as a 'green reducing agent' has been investigated for the reduction of graphene oxide (GO). The extent of reduction was studied by varying the amount of AV. The physical and chemical properties of the GO and reduced graphene oxide (rGO) were investigated using UV-Vis spectrophotometry, FT-IR spectroscopy, High Resolution Transmission Electron Microscopy (HRTEM) and Selected Area Electron Diffraction (SAED). Partially reduced graphene oxide sheets obtained with 7.5 g of AV (rGO-7.5) demonstrated a maximum reduction efficiency of about 73% as evident from FT-IR data. Cyclic voltammetry and electrochemical impedance spectroscopy studies revealed a significant enhancement in current density and a decrease in charge transfer resistance for the rGO-7.5 sample. Moreover, the as prepared rGO-7.5 sample showed a remarkable dye removal ability with a maximum efficiency of ∼98%. The enhanced surface area, π–π interaction and strong electrostatic attraction were correlated with the dye removal capability. The adsorption kinetics were also studied and pseudo second order adsorption phenomena were confirmed. The recyclability of the rGO-7.5 sample was further investigated and an excellent desorption capability was established.